Need for reform of EU banking: Decoupling the solvency of banks and sovereigns - Johannes Pockrandt; Sören Radde (DIW Economic Bulletin, 2012)
Recent developments in Ireland, Greece, and Spain have shown that sovereign debt crises endanger the solvency of domestic banking sectors, while banking crises in turn endanger the solvency of the domestic sovereigns. This diabolic loop between government and bank solvency is exacerbated by the home bias in banks' government bond portfolios, that is, banks' excessive exposure to domestic sovereign debt. Neither current European banking regulation nor plans to implement Basel III in the EU take this interdependence into account. Both treat government bonds of Member States as risk-free, highly liquid assets and exclude them from capital requirements and large exposure regimes. Future EU banking regulation should aim to remedy this. Consequently, EU government bonds could be given risk weights specific to each country. At least in the Euro area, however, a strict limitation of bank investments to cross-border sovereign debt without country-specific risk would be more effective. The advantage of this reform is that it could be integrated into a variety of scenarios for future government refinancing in the Euro area.
Keywords: G18; G21; G32; 330; Basel III; sovereign debt; financial contagion; diabolic loop